Pilomatrixoma of the Cheek: A Case Report - Elhoni, Ashour; ElGehani, Amna (Libyan Journal of Dentistry, 2018)
Pilomatrixoma “Calcifying epithelioma of Malherbe” is a benign calcifying tumor that arises from the hair matrix. It is more common in females and usually presents during the first two decades of life as an asymptomatic, mobile, firm to hard mass. Most of the cases are benign and affect the face. Surprisingly, a preoperative diagnosis of pilomatrixoma is rarely considered by clinicians and often mistaken for other skin-based and subcutaneous lesions. We report a case of pilomatrixoma of the cheek in female Libyan patient, that was clinically diagnosed as a benign salivary gland tumor or reactive lymph node with histopathological findings, and a brief review of the literature. Molar root canal number in more than thirty studies and case reports published so far.